THE INFLUENCE OF KORENA DRAMA ON THE ETHICS OF STUDENTS AND STUDENTS DURING THE COVID-19 PANDEMIC - Musyarrofah, Ika Rahma (JURNAL SOCIUS, 2023)
Korean fever has recently hit Indonesia. Where various groups started talking about something from the country of ginseng. This can indicate that Korea has a good side as an entertainment medium. Korea has a lot of culture that has been exposed so that people around the world know what Korean culture is like. Nowadays Korean culture can be seen from various sources such as the Internet, Film, Drama and Music. Korea tends to have a culture that is able to attract Indonesian people because its culture is not too different from Indonesia. Korean culture has positive and negative values. Therefore, in this discussion, we will discuss "How Korean Dramas Influence Students During the Covid-19 Pandemic". This research aims to: 1). Knowing Student and Student Ethics during the Covid-19 pandemic. 2). How much is influenced by Korean culture.